TERENOWE RADY OŚWIATOWE W PROCESIE USPOŁECZNIANIA EDUKACJI SZKOLNEJ - Kosiorek, Małgorzata (Rocznik Pedagogiczny, 2018)
In Poland, since 1989 thanks to the processes of decentralization and socialization, educational policy is associated with activities carried out at the local level. This is the result of legislation and regulations defining the competences of central and local educational authorities. An example of socialization of education is the formation of educational councils, which are advisory and consul- tative organ. In the article, the author presents the essence and tasks of educational councils, as well as the activity of exemplary councils functioning at the level of a voivodship, county and commune. The analysis indicates that the process of socialization of Polish education, despite the possibilities guaranteed by law, in practice is rare.